Strategi Kebijakan Penguatan Kerukunan Umat Beragama di Kota Bekasi - Catur Pamungkas, Prayogi; Atthahara, Haura; Resmana Adiarsa, Sopyan (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Sinjai, 2024)
Religion can be a unifying tool for the nation of Indonesia through the first principle of Pancasila as its foundation. Religious harmony certainly has a positive impact on the surrounding environment, especially in Bekasi City, which won an award with a tolerant city given by the equivalent institute in 2023. The purpose of this study is to explore the government's policy strategy for strengthening religious harmony in Bekasi City. This research is important to see how the tolerant city of Bekasi City was created so that this research provides insight into public policy in terms of strengthening evidence-based religious communities. This research uses a qualitative approach with a research method design using case studies. Data was collected through direct observation, interviews, archival recordings, and documentation. The results showed that the policy strategy adopted by the Bekasi City Government is multicultural education socialized through social organizations, promotion of interfaith dialogue, and facilitation of activities to strengthen religious harmony.